Інформаційна технологія верифікації паралельних часопараметризованих програм інформаційних управляючих систем - Мороз, Ольга Юріївна; Moroz, O.Yu. (Харків : Харківський національний університет імені В.Н. Каразіна, 2023)
Дисертація присвячена верифікації паралельних програм для інформаційних управляючих систем, що є складною та важливою задачею з багатьма проблемами та викликами

The dissertation is devoted to the development and verification of parallel programs for information management systems, which is a complex and important task with many problems and challenges
Information technology for verification of parallel time-parameterized programs of information control systems
Keywords: Research Subject Categories::TECHNOLOGY::Information technology; технологія верифікації; методи верифікації; паралельні обчислювальні системи; часопараметризовані паралельні програми; мільтипаралельні програми; розподілені системи; верифікація паралельних програм; інформаційні управляючі системи; компіляційна верифікація; декомпіляційна верифікація; семантична верифікація; методи структур семантико-числових специфікацій; методи формального синтезу; часопараметризована модель алгоритму Гауса; verification technology; verification methods; parallel computing systems; time-parameterized multi-parallel programs; distributed systems; verification of parallel programs; information management systems; compilation verification; decompilation verification; semantic verification; methods of structures of semantic-numerical specifications; methods of formal synthesis; time-parameterized model of the Gaussian algorithm